Characterization of Novel Bacterial Strains Associated with EGINA Oil Field Deep-Sea, Port Harcourt, Rivers State, Nigeria - Olukunle, Oluwatoyin Folake; Abe, A. S.; Fajoyegbe, E.; Akinde, S. B.; Kolawole, A. O.; Falese, B. A. (European Journal of Applied Sciences, 2024)
The deep-sea environment has rich microbial resources, which are very much underexploited, which are of economic, industrial and medical importance. The aim of this study is to isolate and identify bacterial species from EGINA oil field deep sea, Port Harcourt, Rivers State. Sediment and water samples were collected with the aid of carousal, and soil auger, and cultivated on both nutrient agar and Actinomycetes isolation agar. Serial dilution and plate methods were used to determine the total heterotrophic bacterial counts. A total of 170 bacterial strains, showing distinct morphologies, were isolated from both water and sediment samples collected at various location at EGINA off-shore. These strains were then categorized into 49 groups, collectively across all the stations based on standard colony morphological characteristics and were isolated and identified by conventional and molecular methods. The mean heterotrophic bacterial counts (measured in colony-forming units, CFUs per mL) from deep-sea water and sediment samples exhibited the highest values at station EGINA-NS-TOP (200×10-2 CFU/mL), followed by the lowest point EGINA-MINI-MID (5.00×10-4 CFU/mL) for water samples. Likewise, highest bacterial counts 1 1 1were recorded at DC6-W1 (200 ×10-2 CFU/g) and lowest bacterial counts (3.00 ×10-6 CFU/g) for sediment samples. Bacillus strains were the most predominant strain isolated with 66.6% frequency of occurrence, some of the Bacillus strains include Bacillus velezensis OOKAAOFFA-1, Bacillus tequilensis OOKAAOFFA-34, Bacillus subtilis OOKAAOFFA-24, likewise Enterococcus gallinarum OOKAAOFFA-49, Brevibacillus halotolerans OOKAAOFFA-36, Stutzerimonas stutzeri OOKAAOFFA-6, Arthrobacter globiformis strain OOKAAOFFA-33 among others. The closest type relationship was seen with the Bacillus, Brevibacillus and Enterobacter strains with branch support of 100% within a clade which also included Bacillus xiamenensis, Bacillus aerius, Bacillus stratosphericus, Arthrobacter globiformis, Enterobacter bugandensis, Enterobacter mori, Brevibacillus formosus, and Brevibacillus halotolerans strains OOKAAOFFA. The results showed the adaptation of the isolated bacteria in the marine environment. Their potentials can be further exploited.